2017
DOI: 10.1002/ejhf.767
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of the presence of macrophages in endomyocardial biopsies of patients with dilated cardiomyopathy

Abstract: It was found that DCM with increased myocardial immune activation was associated with poor long-term outcome. The association between M2 macrophages and collagen formation suggests the phenotypic polarization of macrophages toward M2 may be associated with ventricular remodelling in DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 39 publications
7
50
1
1
Order By: Relevance
“…Recent clinical and experimental evidence has suggested that immune activation and the consequential inflammatory response in the myocardium may be involved in the process of deteriorating cardiac function . Both pro‐inflammatory and anti‐inflammatory infiltrates were associated with poor prognosis in, for instance, dilated cardiomyopathy patients, leading to some profound pathophysiological implications regarding disease progression of cardiomyopathy . Regardless of the trigger of myocardial inflammation, the subsequent immune activation accompanied by a persistence of myocardial inflammatory infiltrates may be a causative factor of the deterioration in severe heart failure .…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical and experimental evidence has suggested that immune activation and the consequential inflammatory response in the myocardium may be involved in the process of deteriorating cardiac function . Both pro‐inflammatory and anti‐inflammatory infiltrates were associated with poor prognosis in, for instance, dilated cardiomyopathy patients, leading to some profound pathophysiological implications regarding disease progression of cardiomyopathy . Regardless of the trigger of myocardial inflammation, the subsequent immune activation accompanied by a persistence of myocardial inflammatory infiltrates may be a causative factor of the deterioration in severe heart failure .…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, DCM was defined as systolic dysfunction [left ventricular ejection fraction (LVEF) < 45%] with ventricular dilation [left ventricular end-diastolic diameter (LVEDD) > 55 mm] in the absence of an apparent secondary cause of cardiomyopathy, such as coronary heart disease, hypertensive heart disease, or valvular heart disease [20]. The exclusion criteria included ischaemic cardiomyopathy, hypertrophic cardiomyopathy, hypertensive heart disease, a history of uncontrollable or untreated hypertension for at least a year before the documentation of LV Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry dysfunction, and other secondary cardiomyopathies such as sarcoidosis and amyloidosis, the presence of significant coronary artery stenosis on angiography and non-ischaemic DCM secondary to valvular heart disease, systemic hypertension, cardiac surgery or acute myocarditis, excessive alcohol abuse, pregnancy, endocrine disease, active infectious disease or collagen disease, medical history of autoimmune disease [12,21]. All subjects gave written informed consent and the protocol was reviewed.…”
Section: Study Populationmentioning
confidence: 99%
“…Furthermore, myocardial inflammation may be seen in other forms of dilated cardiomyopathy as well, and its presence has been recently associated with adverse myocardial remodeling and disease progression. 40 Finally, the radiation exposure from a typical cardiac FDG PET/CT protocol, including a limited whole body FDG PET (skull-base through mid-thighs), is not trivial, however; with the development of three-dimensional acquisition and advent of more sensitive PET systems, it is expected that radiation exposure will continue to decrease substantially in the years to come. 41 …”
Section: Cardiac Fdg Petmentioning
confidence: 99%